2007
DOI: 10.1073/pnas.0701402104
|View full text |Cite
|
Sign up to set email alerts
|

Unc-51-like kinase 1/2-mediated endocytic processes regulate filopodia extension and branching of sensory axons

Abstract: The molecular mechanism and significance of endocytic processes involved in directional axon elongation are not well understood. The Unc-51 family of serine/threonine kinases was shown to be important for axon growth and was also linked to endocytosis, providing an entry point to study this problem. We found that mouse Unc-51-like kinase 1/2 (Ulk1/2) proteins are localized to vesicular structures in growth cones of mouse spinal sensory neurons. RNAi-mediated knockdown of Ulk1 and/or Ulk2 resulted in impaired e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
119
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 25 publications
(33 reference statements)
2
119
2
Order By: Relevance
“…Indeed, recent findings have implicated the mouse Atg1 ortholog, Ulk1/2, in endocytotic processes during neurinogenesis. 32 Paxillin is a multidomain protein and functions as an essential regulatory molecule that couples integrins to the actin cytoskeleton in focal adhesions. 33,34 Several paxillin-associated proteins are involved in regulation of integrin-mediated signaling associated with cell adhesion to extracellular matrix, motility and growth factor responses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent findings have implicated the mouse Atg1 ortholog, Ulk1/2, in endocytotic processes during neurinogenesis. 32 Paxillin is a multidomain protein and functions as an essential regulatory molecule that couples integrins to the actin cytoskeleton in focal adhesions. 33,34 Several paxillin-associated proteins are involved in regulation of integrin-mediated signaling associated with cell adhesion to extracellular matrix, motility and growth factor responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, because Atg1 homologs in other species have been found to participate in nonautophagic processes (Tomoda et al 2004;Ogura and Goshima 2006;Zhou et al 2007), it is unclear whether the lethality of these mutants stems from defects in autophagy or whether this may reflect other functions of Atg1. Here we report the generation of null mutations in Atg7, which encodes the single E1-like enzyme required for activation of both Atg8 and Atg12.…”
mentioning
confidence: 99%
“…Evidence from Drosophila and mammalian cells also indicate that Atg1 proteins have the ability to signal "upstream" to TOR via a feedback loop (32,36). Additionally, it was recently shown that ULK1 can be ubiquitinated and enter into a complex containing the polyubiquitinbinding protein p62 and TrkA NGF receptor, although the function of this pathway in autophagy is currently unknown (37).…”
mentioning
confidence: 99%